Development of Blood Pressure Measurement Device Using The Curve Fitting Method - Ilhan, Ilhan (International Journal of Intelligent Systems and Applications in Engineering, 2019)
In present study, an automatic blood pressure measurement device was developed to perform measurement on the arm. The developed blood pressure measurement device was also used as display and control device. On this device, the curve fitting method, which is a very common numerical analysis method, was used to predict blood pressure. Resistor-Capacitor (RC) and digital filters were preferred to process and filter signal. Various tests were conducted on 21 individuals under the supervision of specialist health personnel. The obtained results indicate that a prediction accuracy of 94.67%, 92.51% and 97.68% can be achieved for systolic and diastolic blood pressure and heart rate values, respectively.